LINKAGE BETWEEN BUILT ENVIRONMENT AND MODE CHOICE (CASE STUDY: TOD PLANNING AREA IN SURABAYA CITY) - Rochmatul Charky, Laily
Transit-Oriented Development (TOD) is a strategy for developing an area which consist of 5D built environment principles that could influence travel behavior. Surabaya City has a plan to provide tram as mass rapid transit in North-South corridor along with TransitOriented Development planning in 4 (four) areas. They are Joyoboyo area, Keputran area, Tunjungan area, and Jembatan Merah area. The aim of this planning is to reduce car usage and encourage community to use public transit. If it is associated with the theory of linkage between built environment and travel behavior, it can be predicted that built environment would influence anyone’s tendency to choose their mode for travel. Based on the background above, this research was conducted to find out the influence of built environment on mode choice in Surabaya’s TOD Planning area. This research has quantitative approach which was done by calculating built environment index in TOD planning area using ArcGIS 10.3, identify relationship between built environment index and mode choice with descriptive quantitative analysis, and calculate the probability of mode shifting based on built environment condition through stated preference questionnaire and binary logit analysis. The result shows that design, accessibility, and distance to transit have an important role to influence someone’s tendency on mode choice either in existing condition or stated preference. In existing condition, those three variables contribute on public transit usage for about 24%. Meanwhile in stated preference condition, distance to transit and headway (accessibility) have negative coefficient for about -0.006 (distance to transit) and -0.122 (headway). sidewalk width and shading (design) have positive coefficient on tram-choice probability for about 2.051 (shading) and 0.24 (sidewalk width).